2016
DOI: 10.1016/j.limno.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Negligible effect of hypolimnetic oxygenation on the trophic state of Lake Jyväsjärvi, Finland

Abstract: Please cite this article as: Kuha, J.K., Palomäki, A.H., Keskinen, J.T., Karjalainen, J.S.,Negligible effect of hypolimnetic oxygenation on the trophic state of Lake Jyväsjärvi, Finland, Limnologica (2016), http://dx.doi.org/10. 1016/j.limno.2016.02.001 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Our results can partially explain the earlier ineffective attempts to mitigate eutrophic conditions by long-term mixing aeration e.g. in Lake Jyväsjärvi (Kuha et al, 2016) as well as provide evidence why the total internal P loading in Lake Tuusulanjärvi (load estimates were based on a modelling approach) has remained at the same level during 20 years of aeration (Horppila et al, 2017).…”
Section: Aeration-induced Increases In Sedimentation Ratesmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results can partially explain the earlier ineffective attempts to mitigate eutrophic conditions by long-term mixing aeration e.g. in Lake Jyväsjärvi (Kuha et al, 2016) as well as provide evidence why the total internal P loading in Lake Tuusulanjärvi (load estimates were based on a modelling approach) has remained at the same level during 20 years of aeration (Horppila et al, 2017).…”
Section: Aeration-induced Increases In Sedimentation Ratesmentioning
confidence: 56%
“…In addition to higher temperature (Rose, 1967;Jones, 1976), the aeration-induced increase in turbulence may enhance the degradation of organic material in the water column by increasing the settling time of particles (Ashley, 1983;Gantzer et al, 2009;Niemistö et al, 2016). Mixing aeration affects temperature (Salmi et al, 2014;Holmroos et al, 2016;Kuha et al, 2016) and additionally increases turbulence in the hypolimnion at least 200 m from the aerator (Niemistö et al, 2016). Despite the significant effect of aeration on the trap material in 2011, no difference in the quality of settling material in near-bottom traps of the deep areas between 2009 and 2016 was detected.…”
Section: Aeration-induced Increases In Sedimentation Ratesmentioning
confidence: 99%
“…The fact that hypolimnion aeration does not always affect the trophic state of a lake has been confirmed by many authors [20,21,33,39,45,46] This was additionally confirmed by the experiment conducted in Lake Jyväsjärvi, where hypolimnion aeration was ceased, and which, in turn, had an extremely negative impact on the oxygen conditions in the hypolimnion, but showed no significant effect on the trophic state of the lake [20]. The results of multiannual studies on the efficiency of lake aeration seem to call into question the paradigm that oxygen controls the release of phosphorus from sediments [47,48].…”
Section: Discussionmentioning
confidence: 78%
“…In aeration methods involving thermal destratification, compressed air is introduced to the waters above the bottom, at the deepest point of the lake, which results in induced rise of the water to the surface and, consequently, mixing of the water mass [15,17,18]. The hypolimnetic oxygenation method is used in deep lakes with thermal stratification [16,[19][20][21][22]. It can be carried out using pneumatic aerators by means of injecting air or pure oxygen into hypolimnion water in a confined space and returning the oxygen-rich water to the lower layer of the lake.…”
Section: Introductionmentioning
confidence: 99%
“…This is of crucial importance for lake ecosystems, where P is one of the most important factors regulating ecosystem productivity and sediment has a large storage of P compared to the water column (Wetzel 2001). Due to the effect of anoxia on internal P loading, artificial aeration or oxygenation (for simplicity, the term aeration is used hereafter) is frequently used in the management of eutrophicated lakes and reservoirs suffering from oxygen deficits (Cooke et al 2005;Kuha et al 2016;Grochowska et al 2017;Horppila et al 2017). However, evidence on the long-term positive effects of aeration on water and sediment quality is obscure (Gächter and Wehrli 1998;Liboriussen et al 2009;Kuha et al 2016;Horppila et al 2017).…”
Section: Introductionmentioning
confidence: 99%